Psychometric Properties for Selected Forms of International Computer Driving License Tests in Jordan, and Equating Their Scores - Alhawari, Arwa; Audeh, Ahmad (Jordan Journal of Educational Sciences, 2008)
This study aimed at investigating the psychometric properties of a selected sample of ICDL tests in Jordan, and equating these tests. To achieve this aim, the concept of equating tests was defined, the required conditions for conducting the equating process were identified, and the design group was explained. In addition, the methods used in equating, were presented. Linear and equipercentile horizontal methods of equating in classical theory and the Rasch model in item response theory (IRT) were used. The psychometric properties (difficulty and discrimination parameters) were presented for the three forms of the seven subtests, which consisted of basic concepts of information technology using the computer and managing files, word-processing, spreadsheets, presentation, and information and communication. With 60 items in the first one and 36 items in each of other subtests, the results of analysis of form properties indicated that their scores should be equated. The sample of study consisted of 1200 examinees for the subtest selected by systematic randomization, distributed into three equale groups randomly. The item parameters and ability parameters were estimated, and the relative effectiveness was discussed for each subtest and all models, depending on both standard error and cross validation to judge the efficiency of equation. The results show that the equation according to the Rasch model is better and more effective according to the previous indicators, followed by the linear and equipercentile respectively.